A dynamic model for costing disaster mitigation policies. Issue 3 (18th April 2013) - Altay, Nezih; Prasad, Sameer; Tata, Jasmine
<x xml:space="preserve">Abstract</x> The optimal level of investment in mitigation strategies is usually difficult to ascertain in the context of disaster planning. This research develops a model to provide such direction by relying on cost of quality literature. This paper begins by introducing a static approach inspired by Joseph M. Juran's cost of quality management model (Juran, 1951) to demonstrate the non‐linear trade‐offs in disaster management expenditure. Next it presents a dynamic model that includes the impact of dynamic interactions of the changing level of risk, the cost of living, and the learning/investments that may alter over time. It illustrates that there is an optimal point that minimises the total cost of disaster management, and that this optimal point moves as governments learn from experience or as states get richer. It is hoped that the propositions contained herein will help policymakers to plan, evaluate, and justify voluntary disaster mitigation expenditures.